O Centro de Lançamento de Alcântara: Abertura para o mercado internacional de satélites e salvaguardas para a soberania nacional - Israel de Oliveira Andrade; Rogério Luiz Veríssimo Cruz; Giovanni Roriz Lyra Hillebrand; Matheus Augusto Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Space activities have been fundamental for defense, communications and meteorology sectors - as well as for observation and positioning operations and for daily life activities. The initial purpose of this paper is to detail the main characteristics of the Brazilian Space Program (PEB, in Portuguese), presenting Brazilian previous experience in space activities and relevant government bodies in the space sector. This text also means to present Alcântara Launching Center (CLA, in Portuguese) marketing points of view and the possible business models for its commercial exploration, considering the opportunities for Brazil to take part in the satellite and microsatellite launching market. After a further investigation about the main challenges for PEB, it concludes that CLA commercialization, as well as the ongoing space governance redesign and the consolidation of Alcântara Space Center (CEA, in Portuguese), represents an important milestone in the strengthening of the space sector in Brazil.
Keywords: F52; F53; H56; O3; 330; Brazilian Space Program; Alcântara Launching Center; space industry; space activities; satellites; aerospace